The Influence of Shopee Affiliate, Shopee Paylater, and Shopee Live Streaming on the Purchase Decision of Fashion Products on the Shopee Application among Students of Solo Technology Christian University - Rumahorbo, Gabriela; Dewi, Adhita Maharani (Sean Institute, 2025)
Technology in the current globalization era brings numerous changes, including the popularity of online shopping across various demographics. Shopee is prominently usedttttt within the community. Multiple factors influence purchasing decisions, particularly for fashion products. This research aims to analyze the impact of Shopee's Affiliate, PayLater, and Live Streaming programs on fashion product purchasing decisions. This quantitative study involves 40 respondents selected through non-probability sampling (purposive sampling) from Solo Christian Technology University, who previously purchased fashion products on Shopee, utilizing questionnaires. Results indicate Shopee Affiliate partially influences purchasing decisions, PayLater has no partial impact, and Live Streaming partially influences purchasing decisions. These three variables collectively affect fashion product purchasing decisions among Solo Christian Technology University students.